REPRODUCTIVE QUALITIES OF COWS WITH THE APPLICATION OF BIOLOGICAL PREPARATIONS - Semenov Vladimir Grigoryevich; Ivanova Tatyana Nikolaevna; Dzhanabekov Kumiskali Dzhanabekovich; Larionov Gennady Anatolyevich; Dzhanabekova Gulmira Kumiskalievna (Scientific Journal of Pedagogy and Economics, 2020)
The pharmaceutical market offers a wide range of various products, many of which are of chemical origin, the bioavailability of which is low. Besides, previously proposed drugs impact only on certain factors of nonspecific resistance, which does not fully ensure the activation of the body's immune system. With secondary immunodeficiencies, potentially pathogenic and pathogenic microorganisms play a significant role in the development of the disease, therefore, antibacterial preparations that can have an immunosuppressive effect are used in the treatment of animals. It is most advisable to prescribe to animals immunostimulants made from natural raw materials with antibacterial drugs. In the combined use, a double hit is applied to the pathogen: the antibacterial drug inhibits the functional activity of the pathogen, increasing its sensitivity to phagocytosis, and the immunostimulant activates the phagocyte, increasing its ability to neutralize the pathogen. A production method for the prevention of postpartum diseases and the realization of the bioresource potential of the reproductive qualities of black-and-white cattle by enhancing the nonspecific resistance of the organism of pregnant cows with a biological product of the Prevention series is proposed. The analysis of the leukocyte blood profile of pregnant and newly-calved cows is carried out. It was established that the use of biological products in critical periods of pregnancy of cows in the 1st and 2nd experimental groups reduced the occurrence of obstetric and gynecological diseases in the postpartum period, and also increased the reproductive qualities of cows. Moreover, the most pronounced corresponding effect was obtained in the 2nd experimental group, where the Prevention series drug was used. The production method for activating cellular factors of nonspecific protection and stress resistance of the organism of black-and-white cattle through the use of a biological product of the Prevention series is proposed. Against the background of intramuscular administration of biological products in the 1st and 2nd experimental groups, physiological leukocytosis, moderate neutropenia with a shift of the nucleus to the right, lymphocytosis and eosinophilia were established, with a more pronounced respective effect of the Prevention series preparation.